Tolerance of the Resistant Biotype Monochoria vaginalis against Different Mode of Action Herbicides - Kurniadie, Denny; Widianto, Ryan; Widayat, Dedi; Umiyati, Uum; Sumekar, Yayan; Nasahi, Ceppy; Sari, Santika; Juraimi, Abdul Shukor; Kato-Noguchi, Hisashi (Research Advances and Challenges in Agricultural Sciences Vol. 5, 2024)
Native to temperate and tropical Asia, Monochoria vaginalis (Burm. f.) C. Presl is an aquatic herbaceous plant in the Pontederiaceae family. In East Asia and the USA, the species is frequently found in paddy fields as a noxious weed that significantly lowers rice output. The objective of the present research was to evaluate the resistance levels of M. vaginalis against three chemical groups of acetolactate synthase (ALS)-inhibitor herbicides and two other groups of herbicides. Additionally, we aimed to investigate the mutations in the ALS gene of the resistant biotype of M. vaginalis. Herbicide dose–response experiments showed that the resistant biotype of M. vaginalis was highly resistant to bensulfuron-methyl, moderately resistant to bispyribac-sodium, had low resistance to penoxsulam and 2,4-D dimethyl ammonium, and was susceptible to sulfentrazone. The nucleotide sequences of the ALS gene of resistant and susceptible biotypes showed 14 base substitutions, which caused two amino acid substitutions: Val-143-Ile and Val-148Ile. It is the first report of the substitutions of amino acids Val-143-Ile and Val-148-Ile in ALS protein. Those mutations may give different resistance spectra against three ALS-inhibitor herbicides: bensulfuron-methyl, bispyribac-sodium, and penoxsulam. It is necessary to elucidate the molecular basis of target-site resistance mechanisms such as the transformation of the ALS gene of M. vaginalis. The employment of herbicide mixtures and/or the rotation of herbicide sites of action should be considered in order to control the biotype of M. vaginalis. Further research is needed to elucidate the molecular basis of target-site resistance mechanisms such as the transformation of the ALS gene of M. vaginalis. It is also necessary to evaluate herbicide mixtures and/or the rotation of herbicide sites of action to control the resistant biotype of M. vaginalis.